Respostas
respondido por:
0
x = 1/3 a P(x) = 1, logo:
P(x) = 3x² + x + 4k
1 = 3(1/3)² + 1/3 + 4k
1 = 3/9 + 1/3 + 4k "simplificando 3/9 fica 1/3
1 = 1/3 + 1/3 + 4k
1 = 2/3 + 4k
4k = 1 - 2 /3
4k = 1 / 3
k = 1/3 dividido por 4 "Conserva o 1°e multiplica pelo segundo invertido"
k =1/3 * 1/4
k = 1 / 12
P(x) = 3x² + x + 4k
1 = 3(1/3)² + 1/3 + 4k
1 = 3/9 + 1/3 + 4k "simplificando 3/9 fica 1/3
1 = 1/3 + 1/3 + 4k
1 = 2/3 + 4k
4k = 1 - 2 /3
4k = 1 / 3
k = 1/3 dividido por 4 "Conserva o 1°e multiplica pelo segundo invertido"
k =1/3 * 1/4
k = 1 / 12
santosroh:
NÃO TEM ESSA ALTERNATIVA
-3.1/9 + 1/3 + 4k = 1
-3/9 + 1/3 +4k = 1
-1/3 + 1/3 +4k = 1
4k = 1
k = 1/4
Perguntas similares
9 anos atrás
9 anos atrás
9 anos atrás
10 anos atrás